Exploring the link between transformational leadership and employee job satisfaction and the mediation effect of employee work motivation among higher education teachers - Bai, Yang; Ghazali, Siti Sabihah (Human Resources Management Academic Research Society (HRMARS), 2024)
This study aims to explore the relationship between transformational leadership and employee job satisfaction and examine the mediating role of employee work motivation in this relationship, with higher education teachers as the research object. Through surveys and analyses of teachers in a series of higher education institutions, a positive association between transformational leadership and employee job satisfaction was found. Further mediation analysis revealed the mediating role of employee work motivation in this relationship, indicating that employee work motivation explains the relationship between transformational leadership and employee job satisfaction to a certain extent. These results not only contribute to our understanding of the relationship between employee happiness and leadership behavior in higher education, but they also serve as a helpful guide for developing initiatives aimed at enhancing both leadership development and the learning environment.